2016
DOI: 10.1186/s12866-016-0706-7
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus genotyping of Giardia duodenalis isolates from children in Oromia Special Zone, central Ethiopia

Abstract: BackgroundGiardia duodenalis is the etiologic agent of giardiasis in humans and other mammals worldwide. The burden of disease is high among children in developing countries where sanitation is inadequate. However, the epidemiology and genetic diversity of this parasite is poorly understood in Ethiopia. This study aimed to determine the prevalence and genetic diversity of G. duodenalis in asymptomatic children in Oromia Special Zone, central Ethiopia.ResultsA total of 286 fresh fecal specimens were collected f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
26
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 41 publications
10
26
3
Order By: Relevance
“…duodenalis , multi-locus genotyping (MLG) employing beta-giardin ( bg ), triose phosphate isomerase ( tpi ) and glutamate dehydrogenase ( gdh ) has been used for genotyping and subtyping G . duodenalis in humans and animals [ 11 13 ]. The aim of the present study was to characterize G .…”
Section: Introductionmentioning
confidence: 99%
“…duodenalis , multi-locus genotyping (MLG) employing beta-giardin ( bg ), triose phosphate isomerase ( tpi ) and glutamate dehydrogenase ( gdh ) has been used for genotyping and subtyping G . duodenalis in humans and animals [ 11 13 ]. The aim of the present study was to characterize G .…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence of sub-assemblage AI in calves in the current study supports the observation that this sub-assemblage predominates in animals than in humans (Xiao and Fayer, 2008;Sprong et al, 2009). The previous molecular studies conducted in Ethiopia showed the occurrence of sub-assemblage AI, AII, BIII and BIV in humans (Gelanew et al, 2007;Flecha et al, 2015;Wegayehu et al, 2016). Hence, the occurrence of assemblage AI isolates both in cattle and humans warrants further investigation due to the zoonotic potential of sub-assemblage within this assemblage.…”
Section: Discussionmentioning
confidence: 88%
“…Molecular studies conducted in Ethiopia have shown the occurrence of assemblages A and B in humans (Gelanew et al, 2007;Flecha et al, 2015;Wegayehu et al, 2016). Mixed infections of assemblages A and F have also been reported (Gelanew et al, 2007).…”
Section: Introductionmentioning
confidence: 93%
“…Recent study conducted on giardiasis showed prevalence of 16.8% in children in Holetta, Sendafa and Chancho [18]. In addition, molecular studies conducted in humans identified C. parvum zoonotic subtype family IIa [19, 20] and G. duodenalis assemblage A and B [18, 21, 22] as the major cause of human cryptosporidiosis and giardiasis in Ethiopia. However, no molecular studies have conducted in sheep to assess the prevalence and genotypes that they harbor.…”
Section: Introductionmentioning
confidence: 99%